2010
DOI: 10.1111/j.1553-2712.2010.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care for Acute Myocardial Infarction in 58 U.S. Emergency Departments

Abstract: Objectives: The objectives of this study were to determine concordance of emergency department (ED) management of acute myocardial infarction (AMI) with guideline recommendations and to identify ED and patient characteristics predictive of higher guideline concordance. Methods:The authors conducted a chart review study of ED AMI care as part of the National Emergency Department Safety Study (NEDSS). Using a primary hospital discharge diagnosis of AMI (International Classification of Diseases, Ninth Revision, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…Tsai et al (2010) ask whether the treatment of AMI is consistent with guidelines from the American Council of Cardiology, and concluded that compliance is “low to moderate” suggesting that there is a great deal of room for improvement. The literature offers many possible reasons for “mistakes” in the choice of procedure to be systematically biased in favor of aggressive and expensive treatment (Chandra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tsai et al (2010) ask whether the treatment of AMI is consistent with guidelines from the American Council of Cardiology, and concluded that compliance is “low to moderate” suggesting that there is a great deal of room for improvement. The literature offers many possible reasons for “mistakes” in the choice of procedure to be systematically biased in favor of aggressive and expensive treatment (Chandra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Results are presented in Section 4, and section 5 concludes. Tsai et al (2010) ask whether the treatment of AMI is consistent with guidelines from the American Council of Cardiology, and concluded that compliance is "low to moderate" suggesting that there is a great deal of room for improvement. The literature offers many possible reasons for "mistakes" in the choice of procedure to be systematically biased in favor of aggressive and expensive treatment (Chandra et al, 2012).…”
mentioning
confidence: 99%
“…The validity of the results depends on the accuracy of the data abstraction. There is a well-defined procedure for training of local hospital representatives and Census Bureau field representatives involved in the data abstraction (8), although the accuracy of data abstraction, especially reporting on medication use, has been questioned in the past based on divergent results of NHAMCS and local ED-based studies (24). However, the staff at CDC and NHAMCS cited the difference in study methodology and national representation of the NHAMCS sample as the primary reason for the divergent results, although small errors in data abstraction are possible (25).…”
Section: ) Proportion (%) Of Acute Myocardial Infarction (Ami) Visitsmentioning
confidence: 99%